Developments in Ground Control in Mining 1981-2020 - Peng, Syd S (Society for Mining, Metallurgy, and Exploration (SME), 2022)
Developments in Ground Control summarizes the objectives, methodology used, and major conclusions reached from papers presented and published in the International Conference on Ground Control in Mining (ICGCM) proceedings from 1981 to 2020. The papers are grouped into 13 aggregate topics.